Lactobacillus salivarius, a Potential Probiotic to Improve the Health of LPS-Challenged Piglet Intestine by Alleviating Inflammation as Well as Oxidative Stress in a Dose-Dependent Manner During Weaning Transition - Sun, Zeyang; Li, Haihua; Li, Yupeng; Qiao, Jiayun (Frontiers in Veterinary Science, 2020)
Intestinal health is a critical issue for piglets during their weaning transition period. Previous reports have emphasized the promise of distinct probiotics in improving the enteric health. Here in this research, a newly isolated Lactobacillus salivarius strain was pretreated to Lipopolysaccharide (LPS)-challenged piglets and its association with integrity of the intestinal barrier coupled with effective dosage were expected to be signified. In the present study, 72 piglets (Landrace × Yorkshiere × Duroc) were randomly allotted to four groups, each group with six replicates. The subjects in the control group were provided with basal diet while those in other tested groups with extra 0.05%, 0.1%, 0.2% L. salivarius, respectively. Fourteen days later, LPS was intraperitoneally injected and sodium pentobarbital was then delivered to euthanize those LPS-challenged piglets. An increase of average daily gain and body weight along with an apparent decline of diarrhea rate were observed in L. salivarius-treated groups. Both 0.1% and 0.2% L. salivarius supplement in total diet had the capability to markedly elevate levels of CAT, GSH-Px, SOD, anti-inflammatory cytokine from the serum as well as tight junction proteins (Claudin-1, Occludin and ZO-1) extracted from intestine in LPS-challenged piglets. These changes were accompanied by the obvious downregulation of D-lactic acid, DAO, MDA and pro-inflammatory mediators in the serum, including IL-1β, IL-6, IFN-γ and TNF-α. Meanwhile, the expression levels of TLR2 and TLR4 in spleen and mesenteric lymph nodes were significantly lower whereas the oxidation-related gene, ho-1 was up-regulated with L. salivarius administration. Our findings suggested that relatively high dose L. salivarius (0.1%-0.2%) could regulate the progression of inflammatory response and oxidative stress when individuals were exposed to LPS, thus probably offering valuable assistance in restoring barrier function and improving overall performance.